SLAM‐associated protein favors the development of iNKT2 over iNKT17 cells. Issue 9 (22nd July 2016) - Michel, Marie‐Laure; Lenoir, Christelle; Massot, Bérangère; Diem, Séverine; Pasquier, Benoit; Sawa, Shinichiro; Rignault‐Bricard, Rachel; Lehuen, Agnès; Eberl, Gérard; Veillette, André; Leite‐de‐Moraes, Maria; Latour, Sylvain
Abstract : SLAM‐associated protein (SAP) is required early in invariant NKT (iNKT) cell development, but its role in later stages is less clear. Here, we reported that signals from SAP are critical for iNKT2 but dispensable for iNKT17 commitment highlighting a new role for SAP on iNKT cell development. Abstract : Invariant NKT (iNKT) cells differentiate in the thymus into three distinct lineages defined by their cytokine and transcription factor expression. Signaling lymphocyte activation molecule (SLAM)‐associated protein (SAP) is essential for early stages of iNKT cell development, but its role during terminal differentiation of iNKT1, iNKT2, or iNKT17 cells remains unclear. Taking advantage of SAP‐deficient mice expressing a Vα14‐Jα18 TCRα transgene, we found that SAP is critical not only for IL‐4 production but also for the terminal differentiation of IL‐4‐producing iNKT2 cells. Furthermore, without SAP, the IL‐17 producing subset is expanded, while IFN‐γ‐producing iNKT1 differentiation is only moderately compromised. Lack of SAP reduced the expression of the transcription factors GATA‐3 and promyelocytic leukemia zinc finger, but enhanced the levels of retinoic acid receptor‐related orphan receptor γt. In the absence of SAP, lineage commitment was actually shifted toward the emergence of iNKT17 over iNKT2 cells. Collectively, our data unveil a new critical regulatory function for SAP in thymic iNKT cell fate decisions.